A Framework for Developing Competencies in Open and Distance Learning - Arinto, Patricia B. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
Many open universities and distance education institutions have shifted from a predominantly print-based mode of delivery to an online mode characterised by the use of virtual learning environments and various web technologies. This paper describes the impact of the shift to open and distance e-learning (ODeL), as this trend might be called, on the course design practices of faculty members at a small single-mode distance education university in the Philippines. Specifically, the paper presents and analyses the faculty’s perspectives on how their course design practices have changed and issues and challenges arising from these changes. The findings suggest that faculty training programs in ODeL should aim to develop a comprehensive range of ODeL competencies in a systematic and coherent way. Based on the findings, as well as research on practitioner development in teaching effectively with technology, a framework for developing ODeL competencies among faculty is proposed. Aside from covering the four areas of change in course design practice identified in the study, the framework also specifies levels of expertise (basic, intermediate, and advanced), indicating degrees of complexity of the knowledge and skills required for each area at each level. All of the competencies listed for all four areas at the basic level comprise the minimum competencies for teaching an online distance education course.